Determinant Factors on Active and Latent Tuberculosis among Children in Surabaya - Ayling Sanjaya1, Dwi Yuni Nur Hidayati2, Susanthy Djajalaksana3, HMS Chandra Kusuma4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Pediatric tuberculosis (TB) is a major health problem in the world and Indonesia. The difficulty of diagnosis is a major factor in eradicating TB in children. Active and latent tuberculosis in children often shows no symptoms so it is difficult to diagnose and affect the treatment. Several determinant factors need to be assessed with the hope of optimal handling of TB in children. Objective: To analyze the determinant factors on active and latent tuberculosis among children in Surabaya. Methods: A case control study was done with 25 cases with TB divided into active TB, Latent TB. Pulmonary tuberculosis was diagnosed using the Indonesian Pediatric Tuberculosis Scoring System. Determinant factors for tuberculosis development were history of contact with a TB patient, age, BCG immunization, knowledge, socioeconomic status and overcrowding living condition. Analysis was done using Fisher’s Exact and Mann-Whitney test. Findings: The characteristics of the study subjects consisting of 16 active TB children and 9 latent TB children. In the group of active TB children the largest population is girls (11 children), whereas in the latent TB group are boys (8 children). There was a significant difference between groups of active TB children and latent TB children (p = 0.000 <0.05). The other factors are showing nothing different in the both of group TB. Conclusion: The most significant determinant factor in active TB and latent TB in children is the appearance infiltrate of chest X-ray where active TB shows filtration and normal appearance in latent TB.